Louisiana's Mixed Legal System - Pascal, Robert (Revue générale de droit, 1984)
The author analyses the Louisiana experience as a basis for suggesting that the codified law methodology which Professor Tancelin favors presupposes a respect for law as the science and art of order for the common good, a respect that decreases as men ignore the ontological bases of human community and regard society as an association of individuals for selfish concerns.